Impact of air pollution control policies on future PM2.5 concentrations and their source contributions in China. (1st December 2018) - Cai, Siyi; Ma, Qiao; Wang, Shuxiao; Zhao, Bin; Brauer, Michael; Cohen, Aaron; Martin, Randall V.; Zhang, Qianqian; Li, Qinbin; Wang, Yuxuan; Hao, Jiming; Frostad, Joseph; et al.
Abstract: To investigate the impact of air pollutant control policies on future PM2.5 concentrations and their source contributions in China, we developed four future scenarios for 2030 based on a 2013 emission inventory, and conducted air quality simulations for each scenario using the chemical transport model GEOS-Chem (version 9.1.3). Two energy scenarios i.e., current legislation (CLE) and with additional measures (WAM), were developed to project future energy consumption, reflecting, respectively, existing legislation and implementation status as of the end of 2012, and new energy-saving policies that would be released and enforced more stringently. Two end-of-pipe control strategies, i.e., current control technologies (until 2017) and more stringent control technologies (until 2030), were also developed. The combinations of energy scenarios and end-of-pipe control strategies constitute four emission scenarios (2017-CLE, 2030-CLE, 2017-WAM, and 2030-WAM) evaluated in simulations. PM2.5 concentrations at national level were estimated to be 57 μg/m 3 in the base year 2013, and 58 μg/m 3, 42 μg/m 3, 42 μg/m 3, and 30 μg/m 3 under the 2017-CLE, 2030-CLE, 2017-WAM, and 2030-WAM scenarios in 2030, respectively. Large PM2.5 reductions between 2013 and 2030 were estimated for heavily polluted regions (Sichuan Basin, Middle Yangtze River, North China). The energy-saving policies show similar effects to the end-of-pipe emission control measures, but the relative importance of these two groups of policies varies in different regions. Absolute contributions to PM2.5 concentrations from most major sources declined from 2017-CLE to 2030-WAM. With respect to fractional contributions, most coal-burning sectors (including power plant, industrial and residential coal burning) increased from 2017-CLE to 2030-WAM, due to larger reductions from non-coal sources, including transportation and biomass open burning. Residential combustion and open burning had much lower fractional contribution to ambient PM2.5 concentrations in the 2017-WAM/2030-WAM compared to the 2017-CLE/2030-CLE scenarios. Fractional contributions from transportation were reduced dramatically in 2030-CLE and 2030-WAM compared to 2017-CLE/2017-WAM, due to the enforcement of stringent end-of-pipe emission controls. Across all scenarios, coal combustion remained the single largest contributor to PM2.5 concentrations in 2030. Reducing PM2.5 emissions from coal combustion remains a strategic priority for air quality management in China. Highlights: The first study on estimate source contributions of coal burning and other key emission sectors to future PM2.5 concentrations in China. Four future scenarios (2017-CLE, 2030-CLE, 2017-WAM, 2030-WAM) for 2030 were developed based on a 2013 emission inventory, and the chemical transport model GEOS-Chem was used to conduct air quality simulations for each scenario. The total PM2.5 concentration at national level are estimated to be 58 μg/m 3, 42 μg/m 3, 42 μg/m 3, and 30 μg/m 3 under 2017-CLE, 2030-CLE, 2017-WAM, and 2030-WAM scenarios, respectively. Across all scenarios, coal combustion remains as the single largest contributor to PM2.5 concentrations in 2030.